Iodine binding with thiophene and furan based dyes for DSCs. Issue 26 (20th June 2018) - Baumann, Alexandra; Cheema, Hammad; Sabuj, Md Abdus; McNamara, Louis E.; Zhang, Yanbing; Peddapuram, Adithya; Nguyen, Suong T.; Watkins, Davita L.; Hammer, Nathan I.; Rai, Neeraj; Delcamp, Jared H.
Abstract : Donor–π-bridge–acceptor dyes with thiophene have been shown to bind I2 leading to diminished dye-sensitized solar cell performances relative to furan based analogues. Abstract : Iodine binding to thiophene rings in dyes for dye-sensitized solar cells (DSCs) has been hypothesized to be performance degrading in a number of literature cases. Binding of iodine to dyes near the semiconductor surface can promote undesirable electron transfers and lower the overall efficiency of devices. Six thiophene or furan containing dye analogs were synthesized to analyze iodine binding to the dyes via Raman spectroscopy, UV-Vis studies, device performance metrics and density functional theory (DFT) based computations. Evidence suggests I2 binds thiophene-based dyes stronger than furan-based dyes. This leads to higher DSC device currents and voltages from furan analogues, and longer electron lifetimes in DSC devices using furan based dyes. Raman spectrum of the TiO2 surface-bound dyes reveals additional and more instense peaks for thiophene dyes in the presence of I2 relative to no I2 . Additionally, broader and shifted UV-Vis peaks are observed for thiophene dyes in the presence of I2 on TiO2 films suggesting significant interaction between the dye molecules and I2 . These observations are also supported by DFT and TD-DFT calculations which indicate the absence of a key geometric energy minimum in the dye–I2 ground state for furan dyes which are readily observed for the thiophene based analogues.